(untitled) (Medical Forum Monthly, 2024)
Objective: To determine and analysis of Antiphospholipid Antibodies in women with Recurrent Miscarriage belongs to District Sukkur. Study Design:: Cross-sectionals study Place and Duration of Study: This study was conducted in the Ghulam Muhammad Mahar Medical College, Sukkur and women attending local health clinics enrolled in this study after taking their informed consent from May, 2012 to August 2013. Materials and Methods: In this study 205 patients were taken. Patient’s whole blood was collected by disposable syringes through vein puncture technique from cubital vein and maximum of 10 ml blood was taken. An aliquot of this blood (4 ml) was transferred in the EDTA containing tube. Immediately after collection plasma was separated and stored at - 40 °C for the measurement of plasma Anti phospholipid and anticardiolipin antibodies level. 5 ml blood was drawn in plain tube and allowed to clot, and then serum was separated and used for blood cholesterol, HDL, LDL and Plasma lipid concentration. Results: In the current research of district Sukkur showed the highest frequency in age group of 26 to 35 years (Table 140). In physical parameters, BMI, calories intake and maternal history of RM of patients and control subjects showed significant (p<0.05) difference. In present study the assessment of antiphospholipids antibodies (aPL) 1.95 % which were significantly different (p<0.05) than controls. Results of anticardiolipin antibodies (aCL) showed 2.43 % prevalence in patients with recurrent miscarriage. Conclusion: The present study indicated that antiphospholipid antibodies and anticardiolipin antibodies were found an indipanded risk for recurrent miscarriage in population of Sukkur.